Land Use and Land Cover Change Dynamics and Perceived Drivers in Rangeland Areas in Central Uganda - Ansyijar Kuule, Derick; Ssentongo, Benard; Magaya, Paul John; Mwesigwa, Gordon Yofesi; Okurut, Isaac Tom; Nyombi, Kenneth; Egeru, Anthony; Stephen Tabuti, John Robert (Land, 2022)
Sustainable rangeland management requires understanding the nature of human-ecosystem interactions and local communities’ perspectives regarding evolving changes. This study integrated perceptions from the local community and remote sensing to characterize the extent and drivers of land use and land cover (LULC) changes in the rangelands of Nakasongola district in Central Uganda. The aim of the study was to determine the perceived drivers of land use and land cover change in of Nakasongola district in the Central Uganda district to support decision making for present and future rangeland management. Satellite imagery for 1985, 1995, 2005, 2015 and 2021 were obtained from the United States Geological Survey (USGS) and analyzed to determine the LULC dynamics. Key informant interviews and focus group discussions (FGDs) were conducted to obtain perceived drivers of LULC. Results showed that by 1985 grassland covered 31.7%, wetlands 26.4%, woodland 11.5% and farmland 7.2% of the total land area. However, by 2021, farmland covered 35.8% of the total land area, wetland 21.6% and had reduced to grassland 18.5 percent. Future LULC projections using a Markov chain model showed that farmland cover will increase by 13.85% while grassland cover will further decline by 9.89% in 2040. Wood fuel extraction, subsistence farming, population growth and overgrazing were perceived as key drivers of LULC change. Both remote sensing techniques and local perceptions were in agreement with the identification of patterns and perceived drivers revealing the inherent value of tacit knowledge resident within the community. This knowledge in addition to remotely sensed information can thus be tapped by the decision leaders to better guide interventions aimed at securing better rangeland health and management.
Keywords: Rangelands; Extent; Local perceptions; Future